Synthesis of Quinoline Based Bisazo Disperse Dyes and Their Dyeing Performance on Polyester Fabric - N. Vashi, Mukesh; G. Mehta, Arvind (Asian Journal of Chemistry, 2010)
Eleven N-(3-hydroxy-4´-R-azobenzene-1´-sulfonamidoazobenzene)-8-quinoline sulfonamides (IVa–k) were prepared by coupling diazotized N-(3-hydroxy-4´-aminobenzene-sulfonamidoazobenzene)-8-quinoline sulfonamide (III) with various coupling components (Ra–k). The compound (I) was coupled with diazotized 4-amino-4´-acetylaminodiphenylsulfonamide giving compound (II) which on hydrolysis gave compound (III). The compounds (IV–k) were characterized by elemental and spectral analyzes and their dyeing performance on polyester fabric was assessed.